2013
DOI: 10.1098/rspa.2012.0631
|View full text |Cite
|
Sign up to set email alerts
|

Angular deficits in flat space: remotely controllable apertures in nematic solid sheets

Abstract: Recent attention has been given to the realization of angular deficits and surpluses in the local ground-state geometry of thin sheets of nematic solids as out-of-plane deformations. Such systems exhibit conical or anti-conical curvature sites, or possibly arrays of such polyhedral corners, in order to satisfy the material's spontaneous strain-generated metric requirements. Here, we turn the angular deficit requirement on its head, and show theoretically and experimentally that by appropriately altering the to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 9 publications
0
20
0
Order By: Relevance
“…Crosslinked liquid crystalline polymers (LCPs) have received much attention as candidates for this purpose since they can exhibit large macroscopic scale mechanical response to different external stimuli such as heat, light, pH, or moisture . Thin‐films of these materials with controlled molecular orientation, defined by the director ( n ), have predominantly been investigated as building blocks to implement a variety of responsive elements or devices . However the thin‐film character of these elements markedly limits the energy available for actuation.…”
Section: Introductionmentioning
confidence: 99%
“…Crosslinked liquid crystalline polymers (LCPs) have received much attention as candidates for this purpose since they can exhibit large macroscopic scale mechanical response to different external stimuli such as heat, light, pH, or moisture . Thin‐films of these materials with controlled molecular orientation, defined by the director ( n ), have predominantly been investigated as building blocks to implement a variety of responsive elements or devices . However the thin‐film character of these elements markedly limits the energy available for actuation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, these particular columnar LCLC films could serve as templates for self-folding materials, since their director "tiling" resembles the patterning studied in models of such films. 43,44 Additionally, the patterns and order induced in theses LCLC films could be transferred to suspended colloids, suspended nanotubes and bacterial systems to create novel metamaterial films. [21][22][23][24][25] …”
Section: -9 |mentioning
confidence: 99%
“…This film was prepared in practice, and it was shown that the slits reversibly open when the film is floating on a hot water bath (Fig. 13d) [35]. Fig.…”
Section: Discrete Patternsmentioning
confidence: 99%